Safety Analysis of the TRIGA 2000 U3Si2-Al Fuel Core Under Reactivity Insertion Accidents - S. Pinem; T. Surbakti; P.H. Liem (Atom Indonesia, 2020)
TheTRIGA 2000 reactor in Bandung is planned to change its fuel type from the TRIGA fuel rod type to the U3Si2-Al plate type of low enriched uranium of 19.75 % with uranium density of 2.96 gU/cc. A study on the neutronic parameters from the equilibrium core has been done. To ensure safe operation of the new fuel,  thermodynamic evaluation of the core needs to be done. The purpose of this study is to conduct a reactor safety analysis of reactivity insertion during withdrawal of the control rod and to study the effect of this reactivity insertion on the power and the maximum temperature of the fuel and the cladding. Reactivity insertion accident is the main factor of the design basis accidents in nuclear reactor design. A simulation of transient for reactivity insertion has been carried out using a coupled neutronic and thermal-hydraulic MTR-DYN code. The code was developed based on three-dimensional multigroup neutron diffusion theory. The coupled space and time-dependent problem were solved by adiabatic model. Transient analysis was performed for a reactivity insertion of 32.33 pcm/s with the assumption that all of the control rods were rapidly withdrawn. For the insertion at a low power of 100 W, the maximum power achieved was 2.74 MW while a maximum power of 2.3 MW was achieved for the power transient of 1 MW. The maximum temperature of the coolant, the cladding, and the fuel for TRIGA 2000 core does not exceed the allowable safety limit for reactivity insertions.